Pengaruh Kualitas Pelayanan dan Harga Terhadap Loyalitas Pelanggan Grab Semarang - Rini Sugiarsih Duki Saputri (CoverAge: Journal of Strategic Communication, 2019)
Online transportation services that currently operate in big cities get human needs wherever and whenever. The emergence of online transportation options has made people switch from conventional transportation to online transportation. This makes entrepreneurs create a variety of online transportation services in order to meet the needs of the community and satisfy customers. Online transportation customers are increasing at this time supported by the brand image of the transportation used so it gives the impression when using it like using private transportation. Determination of affordable online transportation service tariffs with the convenience of the services provided makes this service increasingly loved by the public. This study aims to determine the effect of each independent variable namely service quality and price on the dependent variable of customer loyalty. By taking respondents by purposive sampling 50 Grab online transportation users in the Masters of Communication Studies UNDIP Semarang with a minimum of three times using Grab transportation. Data collection was carried out by survey method using multiple linear regression analysis through SPSS software. The results show that service quality and price affect customer loyalty.